PROFIL PENGELOLAAN SEDIAAN FARMASI, ALAT KESEHATAN DAN BAHAN MEDIS HABIS PAKAI DI PUSKESMAS TULEHU KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH - Zulkarnaen, Farah Safarayana; Nurlina, Nurlina; Zulkarnain, Iskandar (Makassar Pharmaceutical Science Journal (MPSJ), 2024)
Management of pharmaceutical preparations, medical devices and medical consumables is a continuous process starting from the selection, planning, needs, procurement, receipt, storage, distribution, destruction, withdrawal, control and administration needed for pharmaceutical service activities. This study aims to find out about the management system of drug preparations and also medical devices used in serving the community. This research is a descriptive research with a qualitative approach using interview, observation, and document review methods. The result of this study is that there is still a lack of procedures carried out, especially in the storage section which results in damage to drug stocks due to the accumulation of arbitrary goods. In accordance with the standardization, namely, the Regulation of the Minister of Health of the Republic of Indonesia Number 74 of 2016, the management of pharmaceutical preparations, medical devices and consumables at the Tulehu Health Center.